Cutting-Edge Technologies in Breathwork for Learning Disabilities in Special Education - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalampos (Technium Social Sciences Journal, 2022)
The purpose of the current review study is to shed light on the relationship between breathing and learning disabilities, to investigate the efficacy of breathwork as an intervention strategy, and finally, to identify the role of assistive technologies in breathing training interventions. The results of this study revealed a close relationship between breathing problems and learning, mental or/and behavioral disorders. In addition, it was found that breath-control training can help people with various disorders to improve cognitive and metacognitive abilities, to better manage emotional and behavioral problems, and achieve better learning outcomes. Technologies such as robots, virtual reality, mobile apps, and digital games were found to assist breathing training in various ways fostering therapeutic outcomes. We conclude that breathing training should constitute not just an alternative method of intervention but an essential practice for prevention and intervention in daily life, in school settings, at home, and workplace. It is essential to train appropriate breathing habits as early as possible in young children because many of the damaging effects on cognitive functions by disordered breathing can have lasting consequences.